2021
DOI: 10.1101/2021.04.08.439083
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Misrouting of Glucagon and Stathmin-2 Towards Lysosomal System of α-Cells in Glucagon Hypersecretion of Diabetes

Abstract: Glucagon hypersecretion from the pancreatic α-cell is a characteristic sign of diabetes, which exacerbates fasting hyperglycemia. Thus, targeting glucagon secretion from α-cells may be a promising approach for combating hyperglucagonemia. We have recently identified stathmin-2 as a protein that resides in α-cell secretory granules, and showed that it regulates glucagon secretion by directing glucagon towards the endolysosomal system in αTC1-6 cells. Here, we hypothesized that disruption of Stmn2-mediated traf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…This qualitative study demonstrated the plasticity in the network of proteins interacting with glucagon in response to insulin or GABA under high (25 mM) or low (5.5 mM) glucose. Stathmin-2, a member of the family of neuronal phosphoproteins that associates with the secretory pathway in neurons, was identified as a candidate protein for the regulation of glucagon secretion and subsequently shown to modulate glucagon secretion through the lysosomal pathway (140) and may be down-regulated in diabetes in humans (141) and in mice (142). Therefore, disruptions in the routing of glucagon through the lysosomal pathway may contribute to the hyperglucagonemia of diabetes (Figure 4).…”
Section: Novel Proteins In the Regulation Of Glucagon Trafficking And Secretionmentioning
confidence: 99%
“…This qualitative study demonstrated the plasticity in the network of proteins interacting with glucagon in response to insulin or GABA under high (25 mM) or low (5.5 mM) glucose. Stathmin-2, a member of the family of neuronal phosphoproteins that associates with the secretory pathway in neurons, was identified as a candidate protein for the regulation of glucagon secretion and subsequently shown to modulate glucagon secretion through the lysosomal pathway (140) and may be down-regulated in diabetes in humans (141) and in mice (142). Therefore, disruptions in the routing of glucagon through the lysosomal pathway may contribute to the hyperglucagonemia of diabetes (Figure 4).…”
Section: Novel Proteins In the Regulation Of Glucagon Trafficking And Secretionmentioning
confidence: 99%
“…We also noted signi cant downregulation of neuronal differentiation-related genes in the dental pulp. Neuronal differentiation of stem cells is thought to be closely related to the microtubule structure formed by microtubulin [Asadi F, 2022;Vadla P, 2021;Bsibsi M, 2010]. In addition, by reviewing the literature, we found that some studies depicted that microtubulin stathmin was signi cantly differentially expressed in DPSCs and LPS-DPSCs [Zhang X, 2015].…”
Section: Introductionmentioning
confidence: 88%